Penerapan Teknik Search Engine Optimization On Page dan Off Page Pada Berita Kompas.Com - Lisba siella, Liesba; Moh. Zaenal Abidin Eko Putro; Mohammad Fauzy (Jurnalistik dan Media, 2024)
Online media puts emphasize the role of search engines to achieving top rankings viewers, like for example by applying Search Engine Optimisation (SEO) techniques. An effective SEO strategy is not only improves the accuracy of news content, but also share useful information for the readers. This research aims to find out the application of on page and off page SEO techniques at Kompas.com news news portal. The method used in this research is qualitative, which involves indept interview, observation and literature study. The research result shows the application of SEO techniques carried out by Kompas.com media is divided into two SEO, namely on page and off page SEO techniques. The application of on-page SEO techniques is applied in all news bodies, starting from the title, teaser (description), tagging, lead, sub title (heading), image and all of them must have SEO elements. While off page SEO is much worked on backlinks, embed video or social media embed and news recommendations.